Functional divergence of feline calicivirus genotypes shapes virulence and antigenic diversity - Quanhui Yan; Mingjun Ye; Zixiang Zhao; Weihui Li; Zijun Ye; Luying Li; Yan Zhang; Junyao Xiong; Zhixin Lei; Shengbo Cao (Veterinary Microbiology, 2026)

Trade-off between treatment performance and ecological risks in different bioelectrochemical constructed wetlands with iron‑carbon substrates: Insights from sulfamethoxazole and nutrient removal - Mingjun Li; Jifeng Zhao; Xin Zhao; Peihao Yan; Shiyuan Wei; Zizhang Guo; Jian Zhang; Huijun Xie; Haiming Wu (Chemical Engineering Journal, 2026)

A systematic review on the treatment performance, influencing mechanisms and enhancing strategies in constructed wetlands under cold climatic conditions - Zixin Xie; Zhanling Xie; Peihao Yan; Mingjun Li; Jiaqi Meng; Haiming Wu (Process Safety and Environmental Protection, 2026)

Activation of periodate driven by the synergistic interaction between inherent soil Fe and organic matter for adiazine degradation: Mechanisms, soil-type effects, and soil property changes - Yue Zhang; Caixia Yan; Yabing Chen; Yuyan Liu; Mingjun Ding; Peng Wang; Haofeng Liu; Minghua Nie (Journal of Hazardous Materials, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Experimental study on the dynamic characteristics of sandstone-mudstone mixed rockfill based on large-scale cyclic triaxial tests - Jianqing Jiang; Dongyi Ya; Mingjun Tian; Youneng Liu; Guijiang Huang; Sizhou Yan; Jinqiang Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Intensified phosphorus removal in constructed wetlands with different iron‑carbon substrate configurations under micro-aeration regulation: Performance and mechanisms - Jiaqi Meng; Mingjun Li; Shiyuan Wei; Peihao Yan; Zixin Xie; Haiming Wu (Journal of Water Process Engineering, 2026)

Iron ores with contrasting redox properties drive iron biogeochemical cycling to enhance acesulfame and nutrients removal in constructed wetlands - Mingjun Li; Zhiyi Lin; Peihao Yan; Tianzhi Lan; Jian Zhang; Huijun Xie; Haiming Wu (Journal of Hazardous Materials, 2026)

An Overview of Quantum Detection Methods for Shaft-Rate Electric Fields - MingJun Zhou; FangJun Qin; JiuJiang Yan; HaiBo Zhang; LingLong Xia (Journal of Marine Science and Engineering, 2026)
A shaft-rate electric field (SREF) is a weak characteristic signal generated by moving ships in the ocean, serving as a key physical feature in underwater target detection and identification. Based on the generation mechanism of shaft-frequency electric fields, the research progress of traditional detection and extraction methods was systematically reviewed. On this basis, the feasible paths for applying quantum technology in SREF detection were further elaborated by integrating the core characteristics of quantum technology. Results indicated that Rydberg atoms and diamond nitrogen-vacancy centers demonstrate promising feasibility for detecting SREFs, exhibiting significant advantages over conventional methods in sensitivity and precision. Meanwhile, addressing the detection frequency and measurement intensity constituted a crucial breakthrough for the development of quantum technology-based SREF detection. This study aims to provide theoretical foundations and technical feasibility analysis for the quantum detection of SREFs, promoting the paradigm shift in this field from traditional methods to highly sensitive quantum sensing.

Condensate gas adsorption and desorption behavior on continental shale matrix under retrograde condensation effect - Mingjun Chen; Maoling Yan; Yili Kang; Hua Liu; Xiaohu Hu; Gang Xiong; Zhehan Lai; Jiajia Bai (Chemical Engineering Journal, 2026)

Region tracking with smooth control inputs for AUVs based on a piecewise barrier-type function - Yingqi Yan; Xing Liu; Bo Geng; Mingjun Zhang (Ocean Engineering, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

SERPINB1 promotes porcine deltacoronavirus replication by targeting the viral accessory protein NS7a - Junfang Yan; Xinru Liu; Huixin Zhu; Liang Li; Hongye Pan; Renjie Bao; Qiutian Li; Jing Sun; Houhui Song; Mingjun Su (Veterinary Microbiology, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Colloidal electrolyte–mediated dispersion and transport mechanism: Enhancing stability and efficiency of MnO2-based slurry flow battery - Mingjun Nan; Jiaying Yan; Qizhen Cui; Wanyao Sun; Shujie Gao; Xinyu Guo; Wendi Jin; Xiangkun Ma (Chemical Engineering Journal, 2026)

Nitrogen transformation and N2O production pathways under arsenic and cadmium stress in Chongming Island, China - Yinghui Jiang; Guoyu Yin; Minghua Nie; Caixia Yan; Mingjun Ding; Hua Zhang; Mei Lei; Yong Ge (Marine Pollution Bulletin, 2025)

Development of a core streptavidin-bridging amplified ELISA based on p54 epitope for high-sensitivity detection of african swine fever virus antibodies - Jing Sun; Yingshan Zhou; Xingbo Liu; Xiaoxu Du; Jiongze Cheng; Huihua Zheng; Shuonan Pan; Junfang Yan; Xingdong Zhou; Xiaodu Wang; Zixiang Zhu; Dongbo Sun; et al. (The Veterinary Journal, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Agricultural plastic films reshape soil microplastic distribution, nitrogen cycle and ecological risks in facility agriculture - Hao Wang; Gaoxiang Huang; Xiaokang He; Guangchun Shan; Zhenling Li; Mingjun Ding; Chenghong Feng; Caixia Yan (Journal of Hazardous Materials, 2025)

Magnetic field-driven sulfamethazole and nutrients removal in iron‑carbon constructed wetlands: Performance, mechanisms, and resistant risk - Mingjun Li; Xin Zhao; Peihao Yan; Tianzhi Lan; Shiyuan Wei; Jian Zhang; Zizhang Guo; Guowei Zhou; Haiming Wu (Chemical Engineering Journal, 2025)

Human traffic intensity alters the soil microbial community composition, diversity, and structure in subtropical urban green spaces - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Zhaohui Peng; Yangyang Zhang; Safir Ahmad Tamim; Xiuyuan Wang; Zemin Han; Pengcheng Wang (Applied Soil Ecology, 2025)

A reconfigurable mechanical structure inspired by the mechanism of Rubik’s cube: Design, analysis and experiment - Mingjun Song; Yan Qing Wang; Yunlong Li; Quan Wang (Engineering Structures, 2025)

Scenario-based forecasting and multi-objective optimization of low-carbon pathways: A perspective on the composition and carbon emission inventory of urban water treatment plants - Hui Tao; Lin Wang; Mingjun Sheng; Yan Zhang; Qixuan Zhu; Ziyi Li; Tao Lin (Journal of Water Process Engineering, 2025)

Exploring utilization of tourmaline in constructed wetlands to enhance nutrient reduction under fluoride stress: Performance and microbial mechanism - Lingyan Zhao; Jian Zhang; Mingjun Li; Peihao Yan; Jianjun Lian; Zizhang Guo; Haiming Wu (Chemical Engineering Journal, 2025)

Toltrazuril inhibits Toxoplasma gondii by potentially targeting pyrimidine metabolism - An Yan; Kai He; Mingjun Xiong; Xu Wang; Wanxiao Jin; Ruibin Wu; Bolin Xia; Weiwei Sun; Baoliang Pan (Pesticide Biochemistry and Physiology, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Toad’s survivability and soil microbiome alterations impacted via individual abundance - Tian Zhang; Yang Liu; Junde Li; Mingjun Yuan; Chunhan Qiao; Xiao Huang; Xueyao Yang; Bo Gao; Chuan Lou; Yan Yang; Yu Cao (Biologia Futura, 2025)

Weak Fault Feature Extraction for AUV Thrusters with Multi-Input Signals - Dacheng Yu; Feng Yao; Yan Gao; Xing Liu; Mingjun Zhang (Journal of Marine Science and Engineering, 2025)
This paper investigates weak fault feature extraction in AUV thrusters under multi-input signal conditions. Conventional methods often rely on insufficient input signals, leading to a non-monotonic mapping between fault features and fault severity. This, in turn, makes accurate fault severity identification infeasible. To overcome this limitation, this paper increases the number of input signals by utilizing all available measurable signals. To address the problems arising from the expanded signal set, a signal denoising method that combines Feature Mode Decomposition and wavelet denoising is proposed. Furthermore, a signal enhancement technique that integrates energy operators and the Modified Bayes method. Additionally, distinct technical approaches for noise reduction and enhancement are specifically designed for different input signals. Unlike conventional methods that extract features directly from raw input signals, for fault feature extraction and fusion, this study transforms the signals into the time, frequency, and time–frequency domains, extracting diverse fault features across these domains. A sensitivity factor selection method is then employed to identify the sensitive features. These selected features are subsequently fused using Dempster–Shafer evidence theory to construct the final fault feature. Finally, fault severity identification is carried out using the classical grey relational analysis. Pool experiments using the “Beaver II” AUV prototype validate the effectiveness of the proposed method.

Solventless selective self-condensation of cyclopentanone over robust TiO2-SnO2 acid-base bifunctional catalyst - Jiaqi Yan; Jingxuan Zhao; Jing Guo; Zhiyong Yang; Mingjun Xiong; Langsheng Pan; Yongfei Li (Journal of Environmental Chemical Engineering, 2025)

Constructed wetlands for wastewater treatment and reuse: Two decades of experience from China - Zhiyi Lin; Mingjun Li; Peihao Yan; Jian Zhang; Huijun Xie; Haiming Wu (Environmental Research, 2025)

Effect of mineral fertilizer addition on Pinus massoniana Lamb leaf litter decomposition and on amino acid concentration in a subtropical forest - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Peng Zhao Hui; Wang Xiuyuan; Zemin Han; Abebe Assefa Gobena; Ataeei Abdul Rasool; Pengcheng Wang (Plant and Soil, 2025)

Influence of the source and molecular weights on sulfathiazole/sulfadiazine binding in sedimentary dissolved organic matter - Caixia Yan; Fei Zhang; Minghua Nie; Yanqing Luo; Mingjun Ding; Shuhua Nie; John L. Zhou (Journal of Environmental Management, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Enhanced nitrogen removal in constructed wetlands filled with iron-carbon substrates: Reexploring unique roles of iron-cycling and electroactive microorganisms - Mingjun Li; Shiyuan Wei; Ruigang Wang; Xin Zhao; Peihao Yan; Jian Zhang; Huaqing Liu; Zhen Hu; Haiming Wu (Journal of Environmental Management, 2025)

Potential function of plant-growth-promoting endophytic Serratia fonticola CPSE11 from Codonopsis pilosula in phytoremediation of Cadmium ion (Cd2+) - Mingjun Yang; Yunxing Fu; Shu Hu; Feifan Leng; Yan Zhuang; Wenbin Sun; Yonggang Wang (Journal of Environmental Management, 2025)

Interlayer and O-vacancy engineering co-boosting fast kinetics and stable structure of hydrated sodium ammonium vanadate for aqueous zinc-ion battery - Lang Zhang; Dong Fang; Fei Wang; Jianhong Yi; Mingjun Wang; Te Hu; Yan Zhao (Chemical Engineering Journal, 2025)

A review of per- and polyfluoroalkyl substances (PFASs) removal in constructed wetlands: Mechanisms, enhancing strategies and environmental risks - Mingjun Li; Xin Zhao; Peihao Yan; Huijun Xie; Jian Zhang; Suqing Wu; Haiming Wu (Environmental Research, 2024)

Phase-Field Simulation of Counter-Current Imbibition and Factors Influencing Recovery Efficiency - Liu Yang; Mingjun Li; Haitao Zhang; Yan Liu; Zhaoyang Liu; Zhengyan Zhang; Fei Gong; Suling Wang (Transport in Porous Media, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Lightning characteristics and associated microphysical parameters in a strong thunderstorm with an extreme gale - Yan Liu; Fanchao Lyu; Mingjun Wang; Wei Xu; Du Xi; Sulin Jiang (Natural Hazards, 2024)

Copper induces cytotoxicity in freshwater bivalve Anodonta woodiana hemocytes - Mingjun Yan; Xiubao Chen; Tao Jiang; Junren Xue; Karsten Liber; Hongbo Liu; Jian Yang (Chemosphere, 2024)

Combined environmental pressure induces unique assembly patterns of micro-plastisphere biofilm microbial communities in constructed wetlands - Peihao Yan; Shuzhen Zhuang; Mingjun Li; Jian Zhang; Shubiao Wu; Huijun Xie; Haiming Wu (Water Research, 2024)

Effect of mineral fertilizers on microorganisms community characteristic during leaf litter decomposition under Pinus massoniana in a subtropical forest - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Zhiyuan Ma; Jiaoyang Xu; Monira Fayaz; Changjian Zhou; Pujie Wei; Pengcheng Wang (Applied Soil Ecology, 2024)

Reconstruction of Historical Metal Backgrounds in Lacustrine Environments of China Using an Anodonta woodiana “Specimen Bank” - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Degradation of petroleum hydrocarbon contaminants by Rhodococcus erythropolis KB1 synergistic with alfalfa (Medicago sativa L.) - Yan Nan; Ning Zhu; Shangchen Sun; Tianzhu Lei; Xiaopeng Guo; Feifan Leng; Mingjun Yang; Jixiang Chen; Yonggang Wang (Environmental Science and Pollution Research, 2024)

Effect of pyrolysis temperature and molecular weight on characterization of biochar derived dissolved organic matter from invasive plant and binding behavior with the selected pharmaceuticals - Wangyu Wang; Minghua Nie; Caixia Yan; Yulong Yuan; Aoxue Xu; Mingjun Ding; Peng Wang; Min Ju (Environmental Pollution, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Effects of herbicide butachlor application on the growth of periphytic biofilms and nitrogen loss in paddy systems - Yanhui ZHAO; Mingjun LEI; Liandong JING; Fan XIA; Meixia YAN; Jiantong LIU; Yonghong WU; Yunli WU; Chenxi WU (Pedosphere, 2024)

Copper Stress Causes Shell Morphology Changes in Early Juvenile Anodonta woodiana Based on Geometric–Morphometric Analysis - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Tao Jiang; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Visible light-mediated activation of periodate for bisphenol A degradation in the presence of Fe3+ and gallic acid at neutral pH - Yulong Yuan; Wangyu Wang; Minghua Nie; Caixia Yan; Peng Wang; Mingjun Ding (Chemical Engineering Journal, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Correction to: Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2023)

Spatial variations, health risk assessment, and source apportionment of soil heavy metals in the middle Yellow River Basin of northern China - Futian Liu; Xueqiu Wang; Shuang Dai; Jian Zhou; Dongsheng Liu; Qinghai Hu; Wei Wang; Mingjun Xie; Yuexin Lu; Mi Tian; Hao Yan (Journal of Geochemical Exploration, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

CO2 capture performance of CaO-based sorbent modified with torrefaction condensate during calcium looping cycles - Chongcong Li; Xingli Gong; Hao Zhang; Yan Zhang; Mingjun Yang; Bingbing Chen (Chemical Engineering Journal, 2023)

4.3% efficient kesterite solar cell modules - Mingjun Yuan; Chunxu Xiang; Zhen Yan; Hongfei Zhou; Naiyun Liu; Shuxia Wei; Wei Li; Weibo Yan; Chunlei Yang; Hao Xin (Science Bulletin, 2023)

Exposure-lag response of fine particulate matter on intrauterine fetal death: an analysis using a distributed lag non-linear model in Linxia Hui Autonomous Prefecture, China - Wenshan Yan; Mingjun Xie; Xinwei Liu; Shiqiang Han; Juanjuan Xu; Gexiang Zhang (Environmental Science and Pollution Research, 2023)

Characterization of copper binding to biochar-derived dissolved organic matter: Effects of pyrolysis temperature and natural wetland plants - Caixia Yan; Wangyu Wang; Minghua Nie; Mingjun Ding; Peng Wang; Hua Zhang; Gaoxiang Huang (Journal of Hazardous Materials, 2023)

Solar light promoted degradation of bisphenol s in carbonate/peroxymonosulfate system through accelerating singlet oxygen generation - Yulong Yuan; Minghua Nie; Caixia Yan; Leliang Wu; Wenbo Dong; Mingjun Ding; Peng Wang (Chemical Engineering Journal, 2023)

Hydrogen sulfite promoted the activation of persulfate by μM Fe2+ for bisphenol A degradation - Shiyao Chen; Caixia Yan; Minghua Nie; Leliang Wu; Mingjun Ding; Peng Wang (Environmental Science and Pollution Research, 2022)

Host Fish Suitability for Freshwater Bivalve Anodonta woodiana Breeding Programs - Xiubao Chen; Guochao Duan; Mingjun Yan; Hongbo Liu; Tao Jiang; Jian Yang (Fishes, 2022)
The freshwater bivalve Anodonta woodiana is native to China and widely distributed in Asia, Europe, and North America. However, natural populations of A. woodiana in China have dramatically declined recently. Several fish species have been used as potential hosts in breeding programs; nonetheless, the optimal host species is yet to be identified. In this study, we examined the suitability of five potential host fish species (bighead carp, common carp, crucian carp, yellow catfish, and tilapia) for A. woodiana under laboratory conditions. No significant difference was found in the number of glochidia attached to the five fish species; however, tilapia hosted more transformed juveniles than bighead carp, common carp, or yellow catfish (p

Spectral characteristic of the waters with different sizes of particles: impact of water quality and land-use type - Zelan Lv; Peng Wang; Caixia Yan; Minghua Nie; Xiaoying Xiong; Mingjun Ding (Environmental Science and Pollution Research, 2022)

Abdominal Massage Alleviates Skeletal Muscle Insulin Resistance by Regulating the AMPK/SIRT1/PGC-1α Signaling Pathway - Yiran Han; Zeyuan Lu; Shaotao Chen; Chongwen Zhong; Minghui Yan; Heran Wang; Meng Meng; Mingjun Liu (Cell Biochemistry and Biophysics, 2021)
Abdominal massage (AM), a traditional Chinese medicine-based treatment method, has received considerable attention in the recent years. The aim of the present study was to investigate the effect of AM on high-fat diet (HFD)-induced insulin resistance (IR) in comparison with resveratrol (RSV) treatment. Forty-eight male Sprague-Dawley rats were randomly divided into the following four groups: standard chow diet (control group), high-fat diet (model group), HFD + abdominal massage (AM group), and HFD + resveratrol (RSV group). A rat model of IR was established by feeding HFD to rats for 8 weeks followed by treatment with AM or RSV for 4 weeks. The underlying HFD-induced IR molecular mechanisms were studied in rat serum and skeletal muscles. RSV and AM significantly improved glucose intolerance, hyperglycemia, obesity, and significantly reduced lipid accumulation [triglyceride (TC), total cholesterol (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)], adipocytokine [free fatty acids (FFA), adiponectin (ADPN)] and serum pro-inflammatory cytokines (IL-6 and TNF-α) secretion. In addition, AM activated the AMPK/SIRT1 signaling pathway in rat skeletal muscle. In conclusion, our results showed that AM could improve IR by regulating the secretion of adipocytokines, pro-inflammatory cytokines as well as related signaling pathways in the skeletal muscle of rats, which might provide insights into development of new treatment methods for the clinical treatment of IR.

Bisphenol A adsorption behavior on soil and biochar: impact of dissolved organic matter - Yawen Deng; Caixia Yan; Minghua Nie; Mingjun Ding (Environmental Science and Pollution Research, 2021)

Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2020)

Understory vegetation removal reduces the incidence of non-additive mass loss during leaf litter decomposition in a subtropical Pinus massoniana plantation - Wei He; Xin Xu; Chenchen Zhang; Zhiyuan Ma; Jiaoyang Xu; Mingjun Ten; Zhaogui Yan; Ben Wang; Pengcheng Wang (Plant and Soil, 2020)

Retraction Note to: The Critical Role of SRPK1 in EMT of Human Glioblastoma in the Spinal Cord - Zhengbu Liao; Jing Wu; Mingjun Wu; Yi Yan; Haiquan Wang; Chongjie Cheng; Wenyuan Tang (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: The Critical Role of SRPK1 in EMT of Human Glioblastoma in the Spinal Cord - Zhengbu Liao; Jing Wu; Mingjun Wu; Yi Yan; Haiquan Wang; Chongjie Cheng; Wenyuan Tang (Molecular Neurobiology, 2017)

Climate change in Mt. Qomolangma region since 1971 - Xuchao Yang; Yili Zhang; Wei Zhang; Yuping Yan; Zhaofeng Wang; Mingjun Ding; Duo Chu (Journal of Geographical Sciences, 2006)

Characteristics of grassland degradation and driving forces in the source region of the Yellow River from 1985 to 2000 - Linshan Liu; Yili Zhang; Wanqi Bai; Jianzhong Yan; Mingjun Ding; Zhenxi Shen; Shuangcheng Li; Du Zheng (Journal of Geographical Sciences, 2006)